2007
DOI: 10.1111/j.1744-697x.2007.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in the adaptability of herbage species to environmental variations in a long‐term grazing experiment

Abstract: Mixtures of orchardgrass, perennial ryegrass, tall fescue, redtop, Kentucky bluegrass, and white clover were sown in autumn 1973. Two 8‐year grazing experiments were conducted at the National Grassland Research Institute (Nasushiobara, Japan) to determine the effects of grazing intensity and nitrogen levels on pasture ecosystems. These experiments involved two different grazing intensities (1974–1981) and two different nitrogen levels (1982–1989). Large spatiotemporal variations in phytomass due to environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is noted that precipitation had a positive effect on biomass as is the case in much drier regions (mean annual precipitation = 342-580 mm; Ma et al, 2010;O'Connor et al, 2001;Vázquez-de-Aldana et al, 2008;Smart et al, 2007) even at the site of the present study where the growing-season precipitation was as high as 1148-2481 mm. The nonsignificant effect of cumulative stocking density on W, which unexpectedly did not agree with the negative effect of stocking intensity on aboveground biomass (Jones et al, 1995;Yiruhan et al, 2001), can be explained by the fact that the measurements were usually conducted immediately before the rotational stocking periods, that is, when aboveground biomass was recovered from previous stocking. The markedly larger degree of variation in W (33-605 g DM/m 2 ; Figure 4) than that in the number of animals (24-35 cows; see Section 2.1) indicates the occurrence of considerable seasonal and interannual variation in the balance between herbage supply and demand.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is noted that precipitation had a positive effect on biomass as is the case in much drier regions (mean annual precipitation = 342-580 mm; Ma et al, 2010;O'Connor et al, 2001;Vázquez-de-Aldana et al, 2008;Smart et al, 2007) even at the site of the present study where the growing-season precipitation was as high as 1148-2481 mm. The nonsignificant effect of cumulative stocking density on W, which unexpectedly did not agree with the negative effect of stocking intensity on aboveground biomass (Jones et al, 1995;Yiruhan et al, 2001), can be explained by the fact that the measurements were usually conducted immediately before the rotational stocking periods, that is, when aboveground biomass was recovered from previous stocking. The markedly larger degree of variation in W (33-605 g DM/m 2 ; Figure 4) than that in the number of animals (24-35 cows; see Section 2.1) indicates the occurrence of considerable seasonal and interannual variation in the balance between herbage supply and demand.…”
Section: Discussionmentioning
confidence: 97%
“…However, limited information is available on the long-term spatiotemporal variation in aboveground biomass in pastures. Although Jones et al (1995) and Yiruhan et al (2001) reported temporal variation in aboveground biomass in sown pastures under cattle grazing over a 21-year period, they did not quantitatively show the effects of climate and management in the form of a model for aboveground biomass. Although Vázquez-de-Aldana et al (2008) conducted 20-year monitoring of aboveground biomass in a native pasture grazed mainly by cattle and developed models to relate aboveground biomass to climatic variables, they focused only on interannual variation without incorporating seasonal variation into the models.…”
Section: Introductionmentioning
confidence: 98%